2007
DOI: 10.1128/jvi.01513-06
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokine Gene Induction by Human T-Cell Leukemia Virus Type 1 (HTLV-1) and HTLV-2 Tax in Primary Human Glial Cells

Abstract: Infection with human T-cell leukemia virus type 1 (HTLV-1) can result in the development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a chronic inflammatory disease of the central nervous system (CNS). HTLV-2 is highly related to HTLV-1 at the genetic level and shares a high degree of sequence homology, but infection with HTLV-2 is relatively nonpathogenic compared to HTLV-1. Although the pathogenesis of HAM/TSP remains to be fully elucidated, previous evidence suggests that elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 71 publications
3
43
0
Order By: Relevance
“…[22][23][24] CD34 ϩ HPCs (5 ϫ 10 6 ) were injected into sublethally irradiated (350 rads) 4-to 6-weekold NOD/SCID pkrdc mice (The Jackson Laboratory) intravenously through the tail vein, as previously described [25][26][27] to generate HTLV-1-HU-NOD/ SCID or Tax1-HU-NOD/SCID mice. HTLV-1-infected or mock CD34 ϩ HPCs (2 ϫ 10 5 ) were injected into sublethally irradiated (25 rads) 1-to 2-day-old NSG mice (The Jackson Laboratory) intrahepatically to generate HTLV-1-HU-NSG and mock HU-NSG mice as described previously.…”
Section: Ex Vivo Infection Of Cd34 ؉ Cells With Htlv-1 and Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] CD34 ϩ HPCs (5 ϫ 10 6 ) were injected into sublethally irradiated (350 rads) 4-to 6-weekold NOD/SCID pkrdc mice (The Jackson Laboratory) intravenously through the tail vein, as previously described [25][26][27] to generate HTLV-1-HU-NOD/ SCID or Tax1-HU-NOD/SCID mice. HTLV-1-infected or mock CD34 ϩ HPCs (2 ϫ 10 5 ) were injected into sublethally irradiated (25 rads) 1-to 2-day-old NSG mice (The Jackson Laboratory) intrahepatically to generate HTLV-1-HU-NSG and mock HU-NSG mice as described previously.…”
Section: Ex Vivo Infection Of Cd34 ؉ Cells With Htlv-1 and Generationmentioning
confidence: 99%
“…LVs, which coexpress HTLV-1 tax and green fluorescent protein (GFP; pHR'CMV-Tax1/GFP), have previously been described [22][23][24] and were used to transduce CD34 ϩ HP/HSCs ex vivo before inoculation into NOD/SCID mice. Tax1-HU-NOD/SCID mice developed CD4 ϩ malignancies with a slightly accelerated kinetics in comparison with HTLV-1-HU-NOD/SCID mice (Table 1; Figure 2).…”
Section: Lvs Expressing Tax1 Induce T-cell Lymphomasmentioning
confidence: 99%
“…Retrovirus-mediated Tax expression in Jurkat T cells was reported to induce apoptosis, which is mediated by NF-B-activated expression of TRAIL (71). We examined the TRAIL mRNA expression in LV-Tax-infected U251 cells compared with LV-EGFP-infected ones, while IL-6 mRNA expression, which is reported to be increased in Tax-expressing U251 cells (9), was detected to confirm the function of Tax. Results showed that IL-6 mRNA was upregulated in Tax-expressing U251 cells, but the expression of TRAIL mRNA remains unchanged (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are the most abundant cells in the CNS and perform many functions, including maintaining the physical integrity of the blood-brain barrier (BBB), providing nutrients to neuronal cells, and mediating the extracellular ion balance in the CNS (8). A previous study has shown that the in vitro infection of human astrocytes with HTLV-1 results in the release of proinflammatory cytokines (9). Furthermore, it has been found that neuropilin-1 and glucose transporter protein 1 are involved in HTLV-1 infection of U87 astroglioma cells and human primary astrocytes (10).…”
mentioning
confidence: 99%
“…Activation of prosurvival signals such as the NF-B and Akt pathways by Tax 1 plays a critical role in events leading to ATL development and leads to the abnormal expression of several cellular proteins normally involved in apoptosis, cell cycle control, and DNA damage repair (23,34). The upregulation of genes encoding cytokines (1,4,12,33) and growth factors (14,15,27) by Tax 1 is speculated to play a pivotal role in T-cell activation and proliferation and likely contributes to the pathogenesis of both ATL and TSP/HAM.…”
mentioning
confidence: 99%